P6_7 A Shocking Destiny Awaits - Kelly, Aidan; Thompson, Laura; Strachan-Deol, Jack; Knowles, Katie (Physics Special Topics, 2021)
This paper outlines the calculated values for specific heat capacity to allow the ability ”Chaos Reach” from Destiny 2 to be used by a Guardian, along with the total amount of Vex Goblins that can be vaporised from the use of this ability. The calculations were based from properties witnessed from ’true’ lightning, the pain threshold temperature of a human and the composition of the Goblins. It was found that the specific heat capacity of the Guardian is 3.40×10^14Jkg−1K−1 and the number of Goblins that can be vaporised by this ability is 14.9×10^6.